Improving The Speaking Ability of The Tenth Graders of Smk Negeri 1 Singosari Malang Through The Think-Pairsquare Strategy - Isnaini, Moh. Hasbullah (EDUCAFL : E-Journal of Education of English as a Foreign Language, 2012)
This research was conducted to improve the studentsâ speaking ability using the Think-Pair-Square strategy. The research was intended to describe how Think-Pair- Square strategy can improve the speaking ability of the tenth graders of SMK Negeri 1 Singosari Malang. The research adopted a collaborative classroom action research h in which the researcher and the collaborator worked together in conducting the research. The researcher acted as the teacher while the collaborator observed the teacher and the implementation of Think-Pair-Square strategy. This study was conducted in two cycles using the following procedure: planning, implementing, observing, and reflecting. Each cycle consisted of three meetings. The data of the research were gathered through the following instruments: observation checklist, field notes, and questionnaire. The subjects of the research were 31 students of SMK Negeri 1 Singosari Malang. The finding of the research indicated that Think-Pair- Square strategy was successful in improving studentsâ speaking ability. It is suggested that English teachers apply the Think-Pair-Square strategy since it can be a practical contribution on how to improve the studentsâ speaking ability with more practice of using oral communication in their real and natural communication activities, and as relevant knowledge about the teaching of speaking. It is also recommended to the institution, that the findings of the research be used for decision making that the teaching of speaking in this institution has to use Think-Pair-Square strategy. For the future researchers, the findings of this research can become a good reference as strategy to teach speaking.Keywords: Think-Pair-Square Strategy, Speaking Ability